The Effect of Alpha Mangostin on The Expression of TGF-β1, SMAD3, Type I Collagen, Proliferation and Migration of Keloid Fibroblasts - Asri, Ennesta; Rina Gustia; Indah Indria Sari; Jefrizal Wirman; Yufaz Aidi Mahesa (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Keloid is a process of abnormal collagen thickening during wound healing in skin tissue accompanied by the formation of new blood vessels. Many keloid therapy modalities have been developed but the recurrence rate of those treatment still ranged 1-70%. Herbal plants have been developed for various types of treatment, one of which is for treating keloids. Purpose: The alpha mangostin content in mangosteen peel is known to have antifibrotic properties, further research is needed regarding the administration of alpha mangostin on the process of keloid occurrence. Methods: The investigation was conducted in vitro on phase III keloid fibroblast cells. There were two groups, which divided into the control groups and the treatment groups. The control groups and treatment groups were given alpha mangostin extract in concentrations of 20 μM; the sample of this study was 16. For each group after 24h of the incubation, fibroblast cell proliferation was measured by Microtetrazolium (MTT) assay, fibroblast cell migration was measured by scratch assay, SMAD3 expression was measured after immunocytochemical staining, and type 1 collagen was measured by Enzyme-Linked Immunosorbent Assay (ELISA). The Ethics Committee at the Research Ethics Commission of Faculty of Medicine Andalas University has reviewed this research. Result: Alpha mangostin can reduce the average expression of TGF-β1, SMAD3 expression, type 1 collagen, proliferation, and migration. . Conclusion: At concentration of 20 μM, alpha mangostin suppressed TGF-β1 expression, SMAD 3, collagen type 1, proliferation, and migration in keloid fibroblast cell.